Do board sustainability committees contribute to corporate environmental and social performance? The mediating role of corporate social responsibility strategy. (2nd July 2019) - Orazalin, Nurlan
Abstract: The purpose of this study is to investigate the impact of board sustainability committees on environmental and social performance and to examine the mediating effect of corporate social responsibility (CSR) strategy on the relationship between the presence of board sustainability committees and corporate sustainability performance. Using data of U.K. listed firms for the period of 2009–2016, the study employs panel regression analysis and bootstrapping techniques to test study hypotheses. The results suggest that the presence of a sustainability committee improves the effectiveness of CSR strategies. The results also indicate that firms with effective CSR strategies exhibit better environmental and social performance. Further, the empirical results show that the effectiveness of CSR strategy explains the positive relationship between board sustainability committees and corporate environmental and social performance, thus supporting the theoretical framework of the study. The findings of the study shed new light on this research direction and could be of interest to board members, managers, practitioners, investors, policy makers, and regulators that plan to promote sustainability practices and strategies needed for sustainable development.